Influence of single and multiple particle size variation on mechanical and wear behaviour of aluminium silicon carbide composites - Adebisi, Adetayo A.; Maleque, Md. Abdul; Ali , Mohammad Yeakub; Bello, Kamilu Adeyemi (2015)
Lightweight aluminium composite possesses the potential requirement for modern technological applications due to its inherent and superior properties over monolithic materials. This study compares both mechanical and wear behaviour of single particle size (SPS) and multiple particle size (MPS) reinforced 6061 Al-20 wt% SiCp composite. The composite is produced using a bottom pouring stir casting set up. Standard impact and hardness test was conducted to ascertain the energy absorbed before fracture failure and resistance to plastic deformation of the composite. Pin-on-disc test was also investigated at room temperature under dry sliding wear condition. It was observed that the MPS-AMC exhibited superior hardness compared to the SPS-AMC because coarse particle size (CPS) support a greater fraction of applied load while the fine particle size (FPS) and intermediate particle size (IPS) sustain hardening due to dislocation.